Odpowiedzi

2009-11-26T20:12:19+01:00
A)
0,4x + 0,3y = 1,4 / *10
0,1x + 3y = 2,3 / *10

4x + 3y = 14
x + 30y = 23 / =30y

4x + 3y =14
x = 23 - 30y

4 (23 - 30y) + 3y = 14
x = 23 - 30y

92 - 120y + 3y = 14 / -92
x = 23 - 30y

-117y = -78
x = 23 - 30y

y = 1,5
x = 23 - 30 * 1,5

y = 1,5
x = -22

b)
1/2x - 2y = 8 /* 2
2x + 5y = 6

x - 4y = 16
2x + 5y = 6

x = 16 + 4y
2 (16 + 4y) + 5y = 6

x = 16 + 4y
32 + 8y + 5y = 6

x = 16 + 4y
13y = -26

x = 16 + 4y
y = -2

x = 16 + 4 * -2
y = -2

x = 8
y = -2


1 5 1
Najlepsza Odpowiedź!
2009-11-26T20:15:51+01:00
A)
0,4x + 0,3y = 1,4 /*10
0,1x + 3y = 2,3 /*10

4x+3y=14
x+30y=23

4x+3y=14
x=23-30y

4(23-30y)+3y=14
x=23-30y

92-120y+3y=14
x=23-30y

-117y=14-92
x=23-30y

-117y=-78 /*(-1)
x=23-30y

117y=78
x=23-30y

y=2/3
x=23-30*2/3

y=2/3
x=3
-------------------------

b)
1/2x - 2y = 8 /*2
2x + 5y = 6

x-4y=16
2x + 5y = 6

x=16+4y
2(16+4y) + 5y = 6

x=16+4y
32+8y+5y=6

x=16+4y
13y=6-32

x=16+4y
13y=-26

x=16+4y
y=-2

x=16+4*(-2)
y=-2

x=8
y=-2
--------------------------
c)
1/2x - 3/4y = 0 /*4
2/3x + 1 1/4 = 9 /*12 sprawdz czy prawidłowo przepisałeś to rownanie, liczę dla takiej postaci

2x-3y=0
8x+15=9

2x-3y=0
8x=9-15

2x-3y=0
8x=-6

2x-3y=0
x=-3/4

2*(-3/4)=3y
x=-3/4

- 3/2y=3
x=-3/4

y=-1/2
x=-3/4

1 5 1